Implementasi Kinerja Komite Sekolah dalam Manajemen Berbasis Sekolah di SMA Negeri 1 Kota Ternate - Mustafa, Irfandi R Hi; Bakar, Marwia Tamrin; Haji, Sulfi Abdul (Universitas Panji Sakti, 2022)
AbstractThe purpose of this study was to determine the performance of the committee as a deliberative body, as a supporting body, as a controlling body and as a liaison body in school-based management at SMA Negeri 1 Kota Ternate. Descriptive qualitative research method with data collection through observation, interviews and documentation. Data analysis research data reduction, data presentation and conclusions. The subjects of this study were school committees and school principals. The research results showed that: 1). The school committee as a deliberative body was quite good in terms of school planning, program planning (curriculum, PMB and Assessment), management of educational resources (HR, S/P, Budget); 2) The school committee as a supporting body is quite good in terms of managing resources, managing facilities and infrastructure and managing the budget; 3) The school committee acts as a controller in terms of controlling educational planning, monitoring school program planning and monitoring educational output and 4) The school committee as a liaison body was quite good in terms of planning, program implementation and management of educational resources.Keywords: Performance, School Committee, School Based Management.